Biochemical and histological changes associated with Ruzu herbal bitters (RHB) in non-morbid rodents.docx - Kenneth Chukwudi Onyegbula; Gideon Taiwo Oluwaloye; Ayodeji Olanrewaju Badmus (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: In developing countries, the use of herbal preparations has gained much attraction not only for therapeutic purposes but, also for prophylaxis. This study was conducted to determine the effect of a popular Nigeria commercial herbal preparation; Ruzu herbal bitters (RHB) on some biochemical indicators of liver function as well as histology in non-morbid rats. Experimental: Thirty-five adult Wistar rats divided into seven experimental groups (A-G) of five rats each were used for this investigation. Rats in group A were not treated with RHB and served as control. Rats in groups B-G received 0.2 mL, 0.4 mL, 0.6 mL, 0.8 mL, 1.0 mL and 1.2 mL of RHB twice daily by gavage, respectively. All rats were exposed to experimental conditions for two weeks. Blood was collected and analyzed for Total bilirubin (TB), Direct Bilirubin (DB) as well as activities of alkaline phosphatase (ALP), alanine amino transferase (ALT) and aspartate amino transferase (AST). Liver and testicular tissues were processed by standard histological method and stained for microscopy. Results: Rats treated with experimental doses of RHB exhibited lower levels of TB, DB, AST, ALT and ALP in comparison with rats in the control group which had higher values. Rats in the control group had normal liver and testicular tissue morphology while rats given experimental doses of RHB exhibited hepatocellular degeneration, cytoplasmic degeneration, vacuolation, presence of haemorrhage, inflammatory cell infiltration, condensed nuclei and minimal fibrosis in the periportal area. Testicular tissue appeared normal in RHB treated rats. Thus, administration of RHB on non-morbid rats within experimental conditions appears to significantly improve the biochemical indices of liver function (TB, DB, AST, ALT and ALP) but with residual degenerative effects on liver morphology. Recommended applications/industries: RHB is therefore recommended for therapeutics and not for prophylaxis.